Characterization of Pseudomonas fuscovaginae causal agent sheath brown rot of rice in Peninsular Malaysia - Ab Wahab, Mohd Zafri (2014)
Rice (Oryza sativa) is a staple food and strategic crop for economic development in Malaysia. There are several downfall factors that affect rice productivity, which are pests and diseases. Sheath brown rot (SBR) has been highlighted as one of the most important diseases that affect rice plants by contaminating the rice seeds. It causes rot to the sheath, panicle and leaves of rice plants, thus leading to a decline in rice production. In this study, 25 bacteria isolates were studied and characterized morphologically, including hypersensitivity reaction and pathogenicity test, biochemical test as well as molecular identification. These 25 isolates had the characteristics of Pseudomonas fuscovaginae which were fluoresced under UV illumination on King's B Selective (KBS) medium, positive for both hypersensitivity reaction (HR) on Nicotiana tabacum cv. xanthi and pathogenicity tests on Oryza sativa. They also showed positive results for several biochemical reactions such as oxidase, arginine dihydrolase and trehalose utilization tests. Based on these preliminary tests, all isolates were identified as Pseudomonas fuscovaginae. The 16S rDNA sequence analysis showed that all the isolates had 97-99% sequence similarities to P. fuscovaginae in the GenBank database. This result was also supported by the constructed phylogenetic tree with the Acidivorax avenae outgroup. It was noted that all 25 isolates originated from the same node with the P. fuscovaginae group. To evaluate the effect of sheath brown rot pathogen on Malaysian rice varieties, disease severity levels of different bacterial isolates on MR219 variety were determined. Most of the bacterial isolates had virulent and intermediate severity level. Virulent isolate, Tl from Selangor, Malaysia had highest percentage of diseased sheath area. As the effects of sheath brown rot pathogen on Malaysian rice varieties were evaluated, most of the varieties recovered from the disease as they matured. Moreover, results also showed that the panicle's number and grain's weight of infected rice plants were lower than control rice plants but not significant. These findings conclude that under greenhouse conditions, the pathogen of sheath brown rot could not affect Malaysian rice varieties. The information on characteristics of P. fuscovaginae in Peninsular Malaysia and its pathogenicity on Malaysian rice varieties could hopefully be used in future studies especially on Malaysian P. fuscovaginae biology and their control in Malaysia.